Load and temperature dependent sliding wear performance of Binder Jet 3D printed stainless-steel bonded cermet - H.S. Maurya; F. Akhtar; K.G. Prashanth (Journal of Materials Research and Technology)
The present study investigates the dry sliding wear behavior of the TiC-stainless steel-based cermets processed using the Binder Jet 3D Printing technique (BJ3DP). A conventional core-rim microstructure with bimodal TiC grain size was observed in the cermets sintered at 1450 °C, achieving a relative density of 99,5 %. The study explored the effect of loads (5, 10, and 20 N) and temperatures (room temperature, 100, 200, and 300 °C) on the Coefficient of Friction (CoF), wear loss, and wear mechanisms of the sintered cermets. At room temperature, a lower CoF was observed at a 5 N load, corresponding to a lower wear rate for the cermets (3,05 × 10−6 mm3/N-m). Increasing the load at room temperature resulted in a high wear rate of 4,90–5,16 × 10−6 mm3/N-m. Sliding wear tests conducted at 100 °C, 200 °C, or 300 °C resulted in a decreased CoF as compared to room temperature, but a higher wear rate (5,4–8,4 × 10−6 mm3/N-m). At room temperature, the dominant wear mechanisms were fatigue-driven delamination of the compacted debris. However, at elevated temperatures, the predominant wear mechanisms included delamination, adhesive, and oxidative wear. Scanning electron microscopy (SEM) equipped with energy dispersive spectroscopy (EDS) and a 3D surface profilometer was used to investigate the wear mechanisms and properties of the worn surface. The tribological results from the current investigation confirm the feasibility of the BJ3DP process to fabricate TiC-stainless steel cermets parts with optimal wear resistance properties at lower temperatures and loads, highlighting the potential of TiC-based cermets with a low-cost steel binder.